The competitive strategies of poisonous weeds Elsholtzia densa Benth. on the Qinghai Tibet Plateau: Allelopathy and improving soil environment - Zhou, Xijie; Xiao, Yunxing; Ma, Danwei; Xie, Yusi; Wang, Yu; Zhang, Hong; Wang, Yanan (Frontiers in Plant Science, 2023)
Introduction The competitive strategies of plants play a crucial role in their growth. Allelopathy is one of the weapons that plants use to improve their competitive advantage. Methods In order to explore the competitive strategy of a poisonous weed Elsholtzia densa Benth. (E. densa) on the Qinghai-Tibet Plateau (QTP), the effects of decomposing substances of E. densa on growth, root border cells (RBCs) characteristics of highland crop highland barley (Hordeum vulgare L.), and soil environment were determined. Results The decomposing allelopathic effect of E. densa on the germination and seedling growth of highland barley mainly occurred in the early stage of decomposing. The allelopathic effects were mainly on seed germination and root growth of highland barley. After treatment with its decomposing solution, the RBC’s mucilage layer of highland barley thickened, and the RBC’s activity decreased or even apoptosis compared with the control. However, only the above-ground part of the treatment group showed a significant difference. The effects of E. densa decomposed substances on the soil environment were evaluated from soil physicochemical properties and bacterial community. The results showed that soil bacteria varied greatly in the early stage of decomposion under different concentrations of E. densa. In addition, E. densa decomposing substances increased the soil nutrient content, extracellular enzyme activities, and bacterial community diversity. In the process of decomposition, the bacterial community structure changed constantly, but Actinobacteriota was always the dominant phylum. Discussion These results indicated that E. densa might adopt the following two strategies to help it gain an advantage in the competition: 1. Release allelochemicals that interfere with the defense function of surrounding plants and directly inhibit the growth and development of surrounding plants. 2. By changing the physical and chemical properties of soil and extracellular enzyme activity, residual plant decomposition can stimulate soil microbial activity, improve soil nutrition status, and create a more suitable soil environment for growth.